Clinical Application of Human Mesenchymal Stromal Cells for Bone Tissue Engineering - Anindita Chatterjea; Gert Meijer; Clemens van Blitterswijk; Jan de Boer (Hindawi Limited, 2010)
The gold standard in the repair of bony defects is autologous bone grafting, even though it has drawbacks in terms of availability and morbidity at the harvesting site. Bone-tissue engineering, in which osteogenic cells and scaffolds are combined, is considered as a potential bone graft substitute strategy. Proof-of-principle for bone tissue engineering using mesenchymal stromal cells (MSCs) has been demonstrated in various animal models. In addition, 7 human clinical studies have so far been conducted. Because the experimental design and evaluation parameters of the studies are rather heterogeneous, it is difficult to draw conclusive evidence on the performance of one approach over the other. However, it seems that bone apposition by the grafted MSCs in these studies is observed but not sufficient to bridge large bone defects. In this paper, we discuss the published human clinical studies performed so far for bone-tissue regeneration, using culture-expanded, nongenetically modified MSCs from various sources and extract from it points of consideration for future clinical studies.